Maternal magnesium sulfate administration increases early-onset hyperkalemia risk in premature infants: A propensity score-matched, case-control study - Sayu Omori-Shimano; Takahiro Tominaga; Kazushige Ikeda (Elsevier, 2023)
Background: Magnesium sulfate (MgSO4) is a common substance administered to pregnant women with preeclampsia or eclampsia to prevent and treat seizures or gestational hypertension. This study aimed to evaluate whether administering maternal magnesium sulfate increased the risk of early-onset hyperkalemia in preterm infants. Methods: This single-center, propensity score-matched, case-control study examined preterm infants born within 24-36 weeks of gestation using electronic medical records between January 2015 and June 2019, in the Saitama City Hospital, Japan. We categorized infants according to their maternal MgSO4 administration status. After adjusting for perinatal information and maternal treatment, we compared the incidence of the variables, including neonatal hyperkalemia, within 24 h after birth between the matched cohorts. All infants in Model 1 were analyzed separately, while in Model 2 infants with birth weight of less than 1000 g were excluded. Results: We enrolled 421 infants (maternal MgSO4 group, 124; control group, 297). Ninety-five infants in Model 1 and 86 in Model 2 were matched in each group using propensity scores, respectively. In the matched cohorts of both models, infants in the maternal MgSO4 group had a higher hyperkalemia incidence than did those in the control group (42.1% vs. 7.4% in Model 1, 44.2% vs. 5.8% in Model 2, respectively; p < 0.0001). However, there was no relationship between the duration of intrauterine exposure to MgSO4 and early-onset neonatal hyperkalemia incidence. Conclusion: Our study demonstrated that maternal MgSO4 administration, even for a short period of time, may increase the risk of early-onset hyperkalemia in preterm infants. Accordingly, physicians should be cautious when administering serum potassium to infants born to mothers administered MgSO4, especially within 24 h after birth.